Creating Ukrainian youth academic community in the interwar Poland: sources, tasks, centers, activity - Olena Humeniuk (Cхід, 2020)
The purpose of the article is to show the process of creating Ukrainian youth academic community in the interwar Poland. It is analyzed sources of the Ukrainian youth emigration, tasks put before the students (as the main part of young emigrants), foundation and activity of their organizations. Methodology is based on the use of general historical research methods, namely: historical-comparative, typology and system analysis. The article is based on numerous archival documents of the Czech, Polish and Ukrainian archives and also includes wide range of historiography. The most important sources for investigation were periodical issues of Ukrainian youth organizations in Poland, Czechoslovak Republic and other European countries. It is also pointed out in the article peculiarities of academic centers and types of emigrant organizations, influence on to the Ukrainians in the interwar Europe. It is analyzed cooperation between Ukrainian, European and international youth movement.